(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article is devoted to the problem of poetics in M.Utemisov’s poetry. The heroic image of the poet is determined im Makhambet’s potery. The article also discusses the image of Isatay in Mahambet’s poetry. The poems dedicated to Isatai batyr such as «Tarlanym», «Minken er», «Taimannyn uly Isatai», «Isataidyn sozi», «Kyzgysh kus», «Isatai degen agam bar» are analyzed in the article. The paper investigates the artistic skill, poetic language and artistic style of M. Utemisov, it considers lyrical heroes, thematic-ideological issues and the author’s position of M. Utemisov.